Chemokine receptor CXCR3 is important for lung tissue damage and airway remodeling induced by short-term exposure to cigarette smoking in mice - Nie Li; Liu Zhen-jia; Zhou Wei-xun; Xiang Ruo-lan; Xiao Yu; Lu Bao; Pang Bao-sen; Gao Jin-ming (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the role of chemokine receptor CXCR3 in cigarette smoking (CS)-induced pulmonary damage. Methods: CXCR3 knockout (CXCR3-/-) mice were used. Differences in airspace enlargement, mRNA expression of matrix metalloproteinases (MMPs), transforming growth factor (TGF) β1, CXCL10 in lung homogenates, and CXCL10 content in bronchoalveolar lavage (BAL) fluids and homogenates were compared between CXCR3-/- mice and wild-type (WT) mice three days after three-day CS exposures. Results: The linear intercept was significantly less in CXCR3-/- mice than in WT mice (30.1±0.9 μm vs 40.3±2.4 μm, P